Study on ethnoveterinary medicinal plants used by local people inhabiting char area, Kamrup District, Assam, North-East India - Kalita, Chhan Kumar; Mili, Chiranjib; Deka, Mansh Jyoti; Das, Pratisha; Das, Sabebaro Namo (Ecological Questions, 2024)
The inhabitants of char areas of Kamrup district, Assam (India) have relied on medicinal plants to treat various livestock diseases. Due to the lack of proper documentation, these plants have received little attention. Therefore, studying these plant species' diversity, utilisation, and phytochemistry is crucial. By doing so, we can preserve their traditional knowledge and comprehend the possibility of using these plants to develop new drugs. The present investigation documented 30 medicinal plant species belonging to 29 genera and 22 families. These plants were used against the treatment of 12 disease categories. The families Fabaceae and Zingiberaceae, with three species for each, were dominant, while the leaf (22%) and seed (16%) were the most frequently used plant parts. The informant consensus factor (Fic) was found to be highest in neurological disorders and neglected tropical diseases (NTD) with a value of 1.0 each. In contrast, the relative frequency of citation (RFC) was found to be highest in Curcuma longa L. (0.41) and Zingiber officinale Roscoe (0.37). This study provides reliable data on medicinal plants and indigenous ethnoveterinary knowledge that could act as a reference for future researchers dealing with new drug discovery.